Porous Hydrogels: Present Challenges and Future Opportunities - Foudazi, Reza; Zowada, Ryan; Manas-Zloczower, Ica; Feke, Donald L (Langmuir, 2023)
In this feature article, we critically review the physical properties of porous hydrogels and their production methods. Our main focus is nondense hydrogels that have physical pores besides the space available between adjacent cross-links in the polymer network. After reviewing theories on the kinetics of swelling, equilibrium swelling, the structure-stiffness relationship, and solute diffusion in dense hydrogels, we propose future directions to develop models for porous hydrogels. The aim is to show how porous hydrogels can be designed and produced for studies leading to the modeling of physical properties. Additionally, different methods that are used for making hydrogels with physically incorporated pores are briefly reviewed while discussing the potentials, challenges, and future directions for each method. Among kinetic methods, we discuss bubble generation approaches including reactions, gas injection, phase separation, electrospinning, and freeze-drying. Templating approaches discussed are solid-phase, self-assembled amphiphiles, emulsion, and foam methods.